“Implementación de un destilador de agua destilada para el laboratorio de agroindustria de la Universidad Técnica de Cotopaxi Extensión La Maná”. - Allauca Vásquez, William German (2023)
The use of distilled water in laboratories is very common, since this liquid is known as a universal solvent, for this reason it is used for cleaning and sterilizing implements, it is also used in laboratories as a base for injections or other products. The Technical University of Cotopaxi Manna Extension annually spends funds to acquire this product from industries, this creates inconvenience for students who want to do their practices and not have distilled water. The research project has the purpose of implementing a distiller for the laboratory of the Faculty of Agroindustry, which is necessary to obtain the level of purity necessary to meet the needs, for which a conventional distiller project consisting of a boiler made with stainless steel materials, just like its distilled water container. The distillation process follows the principle of the hydrological process, this being that of evaporation, condensation and dripping, in this way it was possible to obtain a favorable result with a purity level of 97%, ideal for carrying out all kinds of work in laboratories, with this distillation equipment. The Faculty of Agroindustry can have 8 liters of distilled water a week without spending funds from the University.